Kelayakan Bahan Ajar Berbantuan Media Flipbook Pada Materi Struktur Atom SMA Fase F - Wongkar, Bregita E.; Tuerah, Jeanne Maria; Kumajas, Jenny (General Chemistry Journal, 2025)
This study aims to test the feasibility of flipbook media-assisted atomic structure teaching materials for Phase F High School. Validation uses a research instrument in the form of an assessment questionnaire that includes format, content, language, practicality, and effectiveness, consisting of 14 criteria. Validation of teaching materials assisted by flipbook media was carried out by seven validators consisting of lecturers in the Department of Chemistry, FMIPAK, Manado State University. The results showed an average total validation (RTV) of 3.11. Based on Khabibah in Yamasari (2010), this teaching material is classified as valid.